Influence of parents on child behavior in dental care (Research, Society and Development, 2019)
The difficulty in pediatric dentistry care, caused by non-collaborative child behavior, may be associated with the stress and anxiety of the parents, who often have gone through negative experiences during dental care. This study aims to show the influence that parents have on their children during pediatric dentistry treatment. A literature review was carried out on the influence of the tutor during dental care and, based on the information collected and on the experience of experts in the area, a booklet was developed with orientations to parents of pediatric dentistry patients. There is considerable influence of parents and guardians in the behavior of children during dental care and those who receive prior treatment orientation are able to obtain better collaboration, improving the professional's performance.